Preference Consumer in Choose Restaurant Dish Noodles in Gianyar Regency Bali - Arcana, I Nyoman; Muliana, I Wayan; Pastini, Ni Wayan; Sudiparwati, Putu Ayu; Febrianto, I Gusti Agung (Borong Newinera Publisher, 2025)
Gianyar Regency has long been known for its traditional cuisine in the form of Ayam Betutu and Babi Guling, but at this time the noodle dish has now developed into one of the people's favorite foods in Gianyar Regency. The characteristic of noodle dishes is their affordable selling price both in stand-alone noodle restaurant chains and in large restaurant chains. This study aims to analyze consumer preferences in noodle restaurants in Gianyar Regency using conjoint analysis with the variables of place, service, atmosphere & parking, safety and hygiene, brand & promotion, price, and product summarized from the results of the research of Fidan et al., (2021); Farooqui and Alwi (2019); Wang et al., (2016); Chua et al., (2020); Kim (2018); Thomadsen (2007); Baharta et al. (2022); Mendoza-Carpio et al., (2021), and Saefudin, et al., (2020). The results of the study show that the variable indicators that are consumer preferences in Gianyar Regency are: strategic location of the restaurant, hygienic food and beverages, attractiveness of the building and dining room, neat and clean appearance of the restaurant staff, adequate parking lot, price according to budget, food price according to expectations, speed of service, product popularity, clean environment around the restaurant, Menu Selection, Restaurant Location Close to Workplace, Brand Image, Word of Mouth Promotion.